PENGARUH PENGAWASAN DAN PEMBERDAYAAN TERHADAP PERILAKU KARYAWAN DALAM PELAYANAN PERIJINAN PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA MEDAN - Sitorus, Monang (Universitas Prof. Dr. Moestopo (Beragama), 2009)
The objectiveresearchand analysisinfluencecontrollingand empoweringtoemployeesbehaviorinserivicepermit inboardofindustryand tradeto Board of Industry and Tradeof Medan City. Thegrand theory controlling testingwriterbyRobbins andCoulter(2005),empoweringtesting writerbyClutterbuckdanKernaghan(2003) andtheoryemployeesbehavior testingwriterbyMarat(1981).Theuseofmethodologyeksplanatorisurveyand allrespondenissensus.Thedatawereanalyzedbyusing PathAnalysis.The infuencethecontrolling (X1)toemployeesbehavior(Y)indirectanddirectis23.8%;lnfuenceempowering(X2) toemployeesbehavior(Y)is15.9%.The effectcontrolling(X1) andempowering(X2) toemployeesbehavior (Y) is39.7%,andtheresidue60.3%influencedtheotherdissimilarfactor(epsilon).